From bench to bedside: elucidating VEGF(R) inhibitor-related heart failure in cancer treatment - Shengkun Peng; MinHong Cai; Hongyu Kuang; Anqi Lin; Qinghua Ma; Xiaoqin Dai; Peng Luo; Yijun Liu; Guo Zhang; Yifeng Bai (Journal of Translational Medicine)
Abstract Background Vascular endothelial growth factor (VEGF) and VEGF receptor (VEGFR) inhibitors play a pivotal role in treating various tumors; however, the clinical characteristics and molecular mechanisms of their associated heart failure (HF) remain incompletely understood. Methods We investigated the epidemiological characteristics of VEGF or VEGFR inhibitors [VEGF(R)i]-related heart failure (VirHF) using the global pharmacovigilance database Vigibase. The phenotypic features and molecular mechanisms of VirHF were characterized using VEGF(R)i-treated mouse models through a combination of echocardiography, histopathological analysis, and transcriptome sequencing. Furthermore, we performed a retrospective analysis of cardiac function parameters in patients undergoing VEGF(R)i treatment at local hospitals. Results In the analysis of 1871 VirHF cases, elderly patients (≥ 65 years) and female subjects demonstrated an elevated risk of occurrence. Experimental studies in mice revealed that both acute and chronic VEGF(R)i administration resulted in reduced left ventricular EF, cardiomyocyte hypertrophy, and myocardial fibrosis. Transcriptomic analysis identified significant dysregulation of multiple key signaling pathways, including DNA repair (R = 0.46), mitochondrial ATP synthesis (R = 0.39), glycogen metabolism regulation (R = 0.45), and proteasome-mediated protein degradation (R = 0.45). Moreover, significant upregulation was observed in inflammatory pathways, specifically those involving IL-1, IL-6, TNF-α, and IRF3/IRF7-mediated immune responses. Clinical cohort analyses demonstrated significant elevations in both cardiac injury biomarkers (NT-proBNP, CK-MB, cTnT) and inflammatory mediators (CRP) following VEGF(R)i administration. Conclusions Our findings present the first comprehensive characterization of VirHF clinical features and elucidate its underlying molecular mechanisms, thereby providing a theoretical framework for optimizing the clinical safety of VEGF(R)i therapy.